2003
DOI: 10.1002/sim.1590
|View full text |Cite
|
Sign up to set email alerts
|

Estimating heterogeneous transmission with multiple infectives using MCMC methods

Abstract: We developed a general procedure for estimating the transmission probability adjusting for covariates when susceptibles are exposed to several infectives concurrently and taking correlation within transmission units into account. The procedure is motivated by a study estimating efficacy of pertussis vaccination based on the secondary attack rate in a rural sub-Saharan community (Niakhar, Senegal) and illustrated with simulations. The procedure is also appropriate to estimate the pairwise transmission probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Other recent approaches for estimating VE S and VE I (e.g., Chu et al, 2004;Halloran et al, 2003) require details about the sequence of infections within each household in order to determine primary and secondary cases. In practice, it may be difficult to obtain information on time of onset or on "who infected whom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent approaches for estimating VE S and VE I (e.g., Chu et al, 2004;Halloran et al, 2003) require details about the sequence of infections within each household in order to determine primary and secondary cases. In practice, it may be difficult to obtain information on time of onset or on "who infected whom.…”
Section: Discussionmentioning
confidence: 99%
“…While direct estimation of vaccine efficacy was not considered in their paper, they did propose two separate forms for including heterogeneity in infectiousness and susceptibility. Without considering transmission probability from community, Chu et al (2004) proposed a logistic regressionbased method that specifies the heterogeneous transmission probabilities among households as a function of vaccination statuses of the infective (only the primary cases) and the susceptible. Their method is based on a Bayesian approach which assumes heterogeneous transmission between and within households and allows Downloaded by [University of Tasmania] at 16:30 09 January 2015 simultaneous estimation of VE S , VE I , and VE T (VE T is the total VE, a measure combining the vaccine's effects on susceptibility and infectiousness).…”
Section: Introductionmentioning
confidence: 99%
“…Parameters are estimated using Markov chain Monte Carlo methods. Reference: [ 26 ] Title: Mortality of a heterogeneous cohort; description and implications. Abstract: A recent model for heterogeneous mortality by Vaupel et al is shown to be based on incorrect definitions.…”
Section: Appendix 1: Abstracts From Literature Searchmentioning
confidence: 99%
“…Parameters are estimated using Markov chain Monte Carlo methods. Reference: (25) Title: Mortality of a heterogeneous cohort; description and implications . Abstract: A recent model for heterogeneous mortality by Vaupel et al is shown to be based on incorrect definitions. An alternative formulation is presented.…”
Section: Abstracts From Literature Searchmentioning
confidence: 99%